2022
DOI: 10.3390/nu14214599
|View full text |Cite
|
Sign up to set email alerts
|

The Ferroptosis Inhibitor Liproxstatin-1 Ameliorates LPS-Induced Cognitive Impairment in Mice

Abstract: CNS inflammation is known to be an important pathogenetic mechanism of perioperative neurocognitive disorder (PND), and iron overload was reported to participate in this process accompanied by oxidative stress. Ferroptosis is an iron-dependent form of cell death, and occurs in multiple neurodegenerative diseases with cognitive disorder. However, the effect of ferroptosis in inflammation-related PND is unknown. In this study, we found that the ferroptosis inhibitor liproxstatin-1 ameliorated memory deficits in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…Inhibition of GPX4 activity leads to the accumulation of lipid peroxides, which is an indicator of ferroptosis in cells. Our investigation found that administering DM significantly elevated GPX4 expression levels in mice with VAP ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 53%
“…Inhibition of GPX4 activity leads to the accumulation of lipid peroxides, which is an indicator of ferroptosis in cells. Our investigation found that administering DM significantly elevated GPX4 expression levels in mice with VAP ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 53%
“…Due to the critical role of lipid peroxidation in ferroptosis, Liproxstatin‐1, which is one of the most investigated lipid peroxidation inhibitors, was used in this study. Our study represents one of the first studies utilizing Liproxstatin‐1 for treatment of cognitive impairment (Li, Sun et al., 2022), particularly in the case of sevoflurane‐induced cognitive disorder. In line with our findings, previous studies have also reported the neuroprotective effects of ferroptosis inhibitors in models of neurodegeneration and brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive deficits following anesthesia are notably prevalent among older surgical patients, an issue known as postoperative cognitive dysfunction (POCD). Approximately 25% of patients over 60 exhibit signs of POCD at 1 week postsurgery, with symptoms enduring beyond three months in 10% of cases (Li, Sun et al., 2022). Given the significance of these findings, our research has specifically concentrated on the geriatric population.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, mind bomb-2 (MIB2) and ferroptosis inhibitor liproxstatin-1 may regulate iron death-related pathways and oxidative stress in the hippocampus, which in turn may repair perioperative BBB damage ( Zhao et al, 2021 ; Li et al, 2022 ). Ferroptosis may be involved in the pathophysiological processes of AD.…”
Section: Potential Adverse Effects Caused By Bbb Damagementioning
confidence: 99%